THE SACRED, SACRILEGE, AND SYMBOLIC BOUNDATIES IN POSTSECULAR, POSTSOCIALIST SERBIA (Religious dialogue and cooperation, 2024)
This paper will strive to address the novel manifestations and roles that sacrilege playsin the postsecular world, and especially how it figuresin the symbolic battles waged in Serbia afterOctober 5, 2000 over which current has the indisputable right to form its postsocialist collectiveidentity – ethnic, ethical, ideological, religious.The focus will be on concrete incidents in Serbianpublic space involving accusations of blasphemy and the ensuing debates, which have arguablyhelpedestablish and maintain the symbolic boundaries in a society. The sample includes caseswhich are mentioned in news portals available online and this corpus of empirical material consistingof media content will be contextualized and subjected to discourse analysis. Of special interestwill be the ways in which both accusations of blasphemy and defenses against these accusationscan serve to draw lines around respective collective identities in symbolic divisions usuallyclosely corresponding with geopolitical ones. The sociocultural problems that will hopefully befurther illuminated are the modalities of the secular status of the state, freedom of religion andfreedom of speech, collective identities (most pertinently ethnic nationalism, especially when combinedwith Eastern Orthodoxy in a postsocialist country), geopolitical influences, and postsecularhybrids (especially establishing which are permissible in a community, and which are perceived asimpure mixing and as such sacrilegious).
Keywords: sacrilege/blasphemy/desecration; the postsecular; symbolic boundaries, religion and identity (ethnicity/gender/sexuality)